A case of localized peritoneal malignant mesothelioma with ovarian metastasis and literature review - Wang, Jingwen; Hu, Rong; He, Qian (La Medicina del Lavoro, 2022)
Peritoneal malignant mesothelioma (PMM) is a rare mesothelial cell-derived malignant tumor, which is clinically distinguished into a localized and diffuse forms, the latter being more common. The onset of PMM is insidious, so it is not easy to make a preoperative diagnosis of PMM. Clinicians must pay more attention to this disease in view of its poor prognosis. In order to improve the understanding of PMM, a case of patient with localized PMM metastasizing to the ovary is reported and discussed, along with a review of relevant literature to further explore the etiology, epidemiology, clinical manifestations, examination methods, diagnosis, treatment and prognosis of PMM.